2003
DOI: 10.1002/gps.1019
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home suicides—a psychological autopsy study

Abstract: Early recognition and adequate treatment of both somatic diseases and mental disorders, particularly depression, as well as early recognition of suicide risk among nursing home residents, are needed in order to prevent suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
3
12

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 35 publications
9
90
3
12
Order By: Relevance
“…For example, it is probable that socio-economic factors such as unemployment status may not cause stress in elderly people. On the other hand, the complex of somatic and mood disorders may be a critical problem in the elderly because the incidence rate of somatic disorders increases as they grow old [44]. Finally, there may be some studies that could not be characterized by the keywords used in the present study, but conducted with designs similar to psychological autopsy studies.…”
Section: Limitationsmentioning
confidence: 82%
“…For example, it is probable that socio-economic factors such as unemployment status may not cause stress in elderly people. On the other hand, the complex of somatic and mood disorders may be a critical problem in the elderly because the incidence rate of somatic disorders increases as they grow old [44]. Finally, there may be some studies that could not be characterized by the keywords used in the present study, but conducted with designs similar to psychological autopsy studies.…”
Section: Limitationsmentioning
confidence: 82%
“…As for non-mental illness, although problems with physical health and level of functioning augment the risk of suicidal behaviors, especially for males , many studies suggest that their effects are generally mediated by mental health factors, most notably depression (Conwell & Thompson, 2008;Conwell et al, 2002;Préville, Hebert, Boyer, Bravo, & Seguin, 2005;Suominen et al, 2003). Some studies have found that medical lethality may be linked with lethality of suicide attempts (Power, Cooke, & Brooks, 1985), but this correlation has not yet been proven in a manner that is independent of the incidence of factors related to depression.…”
Section: Studymentioning
confidence: 93%
“…The most common findings included ASCVD (43), neurodegenerative disease (19), non-ASCVD (13), bronchopneumonia (12), cerebrovascular accident (12), blunt force trauma of the trunk (7), mental retardation/schizophrenia/depression (6), and 5 cases each of COPD, decubitus ulcers, blunt force trauma to the head, and blunt force trauma of the neck (Table 10). …”
Section: Additional Medical Findingsmentioning
confidence: 99%